2015
DOI: 10.1152/jn.00970.2014
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive mild traumatic brain injury induces ventriculomegaly and cortical thinning in juvenile rats

Abstract: Goddeyne C, Nichols J, Wu C, Anderson T. Repetitive mild traumatic brain injury induces ventriculomegaly and cortical thinning in juvenile rats. J Neurophysiol 113: 3268 -3280, 2015. First published February 18, 2015 doi:10.1152/jn.00970.2014.-Traumatic brain injury (TBI) most frequently occurs in pediatric patients and remains a leading cause of childhood death and disability. Mild TBI (mTBI) accounts for nearly 75% of all TBI cases, yet its neuropathophysiology is still poorly understood. While even a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 108 publications
3
44
0
Order By: Relevance
“…By contrast to reports in adult mice (Cantu et al ., ), recordings from pyramidal neurons in juvenile mice revealed a lack of generalized hyperexcitability (Goddeyne et al . ; Nichols et al . ) and the presence of unique excitatory and inhibitory synaptic bursts following CCI (Nichols et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast to reports in adult mice (Cantu et al ., ), recordings from pyramidal neurons in juvenile mice revealed a lack of generalized hyperexcitability (Goddeyne et al . ; Nichols et al . ) and the presence of unique excitatory and inhibitory synaptic bursts following CCI (Nichols et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously found that juvenile mice respond uniquely after TBI with a lack of generalized hyperexcitability (Goddeyne et al . ; Nichols et al . ) and the presence of unique synaptic bursts following more severe TBI (Nichols et al .…”
Section: Introductionmentioning
confidence: 99%
“…254 Finally, pediatric populations exhibit different responses to adults experiencing a similar head trauma, 255 and limited studies have been conducted assessing younger populations. 235,236,256,257 Conclusions Long-term cognitive impairments following CNS injury and in neurodegenerative diseases have been associated with prolonged oxidative stress conditions 131,258 and impaired signal conduction along dysmyelinated axons. 259 Further, persisting behavioral deficits after TBI have been associated with progressive activation of astrocytes 260 and microglia.…”
Section: Barriers To Clinical Translationmentioning
confidence: 99%
“…However, there is a disproportionate paucity of pediatric mTBI research in preclinical models for translation to the human condition. A handful of preclinical studies report acute cortical atrophy, axonal swelling, axonal disconnections [17], cortical thinning, and ventricular enlargement [18], in addition to edema and gliosis following pediatric and juvenile rmTBI [19]. Another preclinical pediatric rmTBI study reported early evidence of axonal injury and microglial activation, as well as long-term associative learning deficits after 3 weeks and 3 months, respectively [20].…”
Section: Introductionmentioning
confidence: 99%